2017
DOI: 10.1093/ofid/ofx058
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Arthritis of the Fingers and the Wrist: Can We Shorten Antimicrobial Treatment Duration?

Abstract: Background.Pyogenic arthritis of the small joints of the hand and wrist is a known but poorly described entity. The objective of this work was to characterize the clinical presentation, antimicrobial treatment, and surgical interventions of native small joint arthritis (SJA) treated in our tertiary center.Methods.According to predefined variables, medical records of adult patients with SJA treated in a Swiss university hospital between 2005 and 2013 were retrospectively analyzed.Results.The median age of 97 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 18 publications
1
44
0
2
Order By: Relevance
“…In septic arthritis of the native nger joints, S. aureus was the most frequent isolated microorganism, followed by Streptococcal species; further, MRSA was detected in lesser number of cases than was MSSA [1,7,10,19,20]. Thus, conventional narrow-spectrum antibiotics such as penams and the rst-generation cephalosporins are recommended in primary cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In septic arthritis of the native nger joints, S. aureus was the most frequent isolated microorganism, followed by Streptococcal species; further, MRSA was detected in lesser number of cases than was MSSA [1,7,10,19,20]. Thus, conventional narrow-spectrum antibiotics such as penams and the rst-generation cephalosporins are recommended in primary cases.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons can choose either primary extensive resection or sequential gradual resection as long as the debridement extends beyond the necrotic tissues. Besides, the duration of antibiotics use could be shortened according to recent studies [10,22]. Thus, future studies, including large cohorts (to match age and treatment delay) and focusing on the extent of surgical debridement and shorter duration of antibiotics use are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate antibiotic treatment is indispensable and should be adjusted after close monitoring and culture results. A study of 97 patients by Meier and colleagues 40 in 2017 found that the median antimicrobial treatment duration was 14 days. Surgical drainage should be done with care to avoid contamination of surrounding structures or injury to nearby structures, and patients should be advised that some degree of joint stiffness often is inevitable, especially in patients who presented after a few days of infection or whose proximal interphalangeal joints are affected.…”
Section: Septic Arthritis: Patients With Septic Arthritismentioning
confidence: 99%
“…1 It occurs less frequently than large joint septic arthritis and is less likely to cause laboratory-result abnormalities and abnormal vital signs. 2 Water bath ultrasonography allows immediate, high-quality evaluation of the smaller joints of the body, which can quickly identify signs of septic arthritis not appreciable on physical examination. 3,4 Author affiliations: From the Department of Emergency Medicine, University of Kansas Health System, Kansas City, KS.…”
Section: Diagnosismentioning
confidence: 99%